Bio-Évaluation De La Qualité Des Eaux De Surface D’oued Beht (Maroc) Indice Biologique Global Des Réseaux De Contrôle Et De Surveillance (IBG-RCS) - Lamhasni Nihad; Chillasse Lahcen; Timallouka Mohamed (European Scientific Journal, ESJ, 2017)
The present study concerns the biological assessment of Beht’s river quality in Morocco during the period Mai-June of 2014 using the standard Global Biological Index of Control and Surveillance Networks (GBICSN).Thus twelve sampling stations were chosen for the determination of the impact of agricultural and urban waste of Beht’s area on the biological waters quality of this river. As results this biological approach showed downgrading notes of the biological index from the watershed’s uphill to its downstream reflecting this way the deterioration of water quality with increasing anthropogenic action and inputs.